Application of Dermal Equivalent Accelerates the Healing of Thermal Injuries (Experimental Study) - Zubov, Dimitri A.; Vasyliev, Roman G.; Rodnichenko, Angela Ye.; Klymenko, Pavel P.; Ostapchenko, Lyudmyla I. (Problems of Cryobiology and Cryomedicine, 2013)
N/AProbl Cryobiol Cryomed 2013; 23(3):287–291.